Phenotypic Characterization of Zinc and Iron Rich Cytoplasmic Male Sterile Lines of Rice - Mashiat, S; Ivy, NA; Rasul, MG; Haque, MM; Raihan, MS (Annals of Bangladesh Agriculture, 2019)
A total of 23 cytoplasmic male sterile (A) lines with their corresponding maintainer (B) lines of rice were used for the experiment. The experiment was carried out in completely randomized block design with two replications in the experimental field of the Department of Genetics and Plant Breeding, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur during Aman season 2017. A total of 13 characters were studied. BRRI 1A, IR 62 A and IR 68888 A had shown both the earliness and dwarfness character. The higher yield per plant was obtained from Gan 46 A, Straw A, Sugundhi dhan 2A, IR 68888 A and BRRI 1A. Zinc and Iron content of phenotypically best performed rice genotypes were determined in brown condition by using X-Ray Fluorescence technique (XRF). Small differences between Genotypic and Phenotypic coefficient of variation were recorded for all the characters studied which indicated less influence of environment in expression of the characters. Correlation study revealed that selection based on weight of filled grain per panicle, thousand grain weight and number of grains per panicle would be effective for increasing grain yield per plant. Path co-efficient study showed that direct selection based on weight of filled grain per panicle and number of effective tiller per plant would be indicator for yield improvement. Considering yield and studied characters IR 58 A, IR 62 A, IR 68888 A, Gan 46 A and BRRI 1A could be used as cytoplasmic male sterile line which is enriched with zinc and iron. Ann. Bangladesh Agric. (2019) 23(2) : 105-114